A new species of bent-toed gecko, genus Cyrtodactylus Gray, 1827 (Reptilia: Squamata: Gekkonidae), from Jawa Timur Province, Java, Indonesia, with taxonomic remarks on C. fumosus (Müller, 1895) - Hartmann, Lukas; Mecke, Sven; Kieckbusch, Max; Mader, Felix; Kaiser, Hinrich (Zootaxa, 2016)
A new species of the gekkonid lizard genus Cyrtodactylus Gray, 1827 is described from Klakah, Lumajang Regency, Jawa Timur Province, Java, Indonesia. Cyrtodactylus klakahensis sp. nov. can be distinguished from all other congeners by the presence of (1) a deep precloacal groove in males, (2) three rows of enlarged precloacofemoral scales, of which the third row bears 37–38 pores in males, (3) three or four rows of enlarged scales between the precloacofemoral scale rows and the cloaca, forming distinct chevrons, (4) raised and strongly keeled dorsal tubercles in 15–19 rows at midbody, (5) an indistinct lateral fold, (6) 17–20 subdigital lamellae under the 4th toe, and (7) subcaudal scales which are not transversely enlarged. Cyrtodactylus klakahensis sp. nov. is only the third bent-toed gecko species described from Java, indicating that the diversity of this genus on this island has been neglected in the past. Furthermore, we confirm that C. fumosus (Müller, 1895) is a species that possesses a precloacal groove in males and is most likely restricted to northern Sulawesi. That species is defined by a single female holotype (NMB-REPT 2662). Specimens in museum collections catalogued as C. fumosus from localities elsewhere are misidentified and likely represent undescribed species.